Why is patch management necessary?. Issue 7 (July 2018) - Dennis, Colin
Abstract : If you're a UK business that relies on any form of technology, then patch management should be at the top of your 'to do' list. More and more companies rely on a form of software and/or IT infrastructure to streamline their processes, maximise return on investment and store valuable data. If you're a UK business that relies on any form of technology, then patch management should be at the top of your 'to do' list. As technology evolves, so does cybercrime. The more detailed and comprehensive the approach you take to patch management, the more you are reducing the risk of a vulnerability being exploited and data breaches being made, explains Colin Dennis of OGL.